Time-lagged and cumulative effects of drought and anthropogenic activities on China's vegetation greening from 1990 to 2018 - Yuxi Wang; Tiantian Chen; Qiang Wang; Li Peng (International Journal of Digital Earth, 2023)
Previous studies have confirmed the time-lagged and cumulative effects of drought and anthropogenic activities on vegetation growth, but these studies focus on the time-lagged effect of drought and are poorly known how vegetation productivity responds to anthropogenic activities. Here, based on the reconstructed Normalized Difference Vegetation Index, the Standardized Precipitation Evapotranspiration Index and land use degree comprehensive index, we diagnosed the spatiotemporal pattern of vegetation and drought, investigated time-lagged and cumulative effects of drought and anthropogenic activities over China through the month where the maximum correlation coefficient occurred. It revealed that the browning trend of 32.21% of vegetated lands was covered by overall greening, especially in northwestern China. Drought intensified with a rate of 0.0014/year. 66.41% and 54.57% of the vegetated lands had time-lagged and cumulative response to drought, with a shorter timescales of 1–4 months, indicating the higher sensitivity of vegetation growth to drought. There was a U-shaped relationship between moisture conditions and vegetation response time. 49.9% of China's vegetation showed time-lagged effects to anthropogenic activities, with a longer timescales of 6–10 years, demonstrating that anthropogenic activities triggered ecological changes but vegetation ecosystems cannot keep pace. The accumulated and time-lagged years declined with increased land use intensity.